Blenderized food tube feeding in patients with head and neck cancer. (31st August 2021) - Spurlock, Amy Y.; Johnson, Teresa W.; Pritchett, Ali; Pierce, Leah; Hussey, Jenna; Johnson, Kelly; Carter, Holly; Davidson, Stephen L.; Mundi, Manpreet S.; Epp, Lisa; Hurt, Ryan T.
Abstract: Background: Patients with headand neck cancer (HNC) are at high risk for malnutrition before and during chemoradiation treatment. Many will also require tube feeding to address declines in energy intake, weight, and quality of life (QOL) caused by the impact of treatment on gastrointestinal (GI) symptoms. Blenderized tube feeding (BTF) may ameliorate these adverse conditions. Methods: In this open‐label, prospective pilot study, 30 patients with HNC who required feeding tube placement were recruited to switch from standard commercial formula after 2 weeks to a commercially prepared BTF formula. Weight, body mass index (BMI), GI symptoms, and QOL scores were tracked for 6 weeks from the first week of feeding tube placement. Results: Of the 16 patients who completed the 6‐week assessment period, weights and BMI scores for 15 patients trended upward. For most patients, QOL and oral intake increased and GI symptoms decreased over the 6‐week period, particularly during weeks 3 and 4, when the impact of treatment is particularly exacting on patients with HNC. Conclusion: BTF effectively mitigated weight loss, GI symptoms, QOL scores, and total energy intake in this group of patients with HNC who received tube feeding for 6 weeks.